Numerical Optimization - Nocedal, Jorge; Wright, Stephen J. (Springer, 2006)
This is a book for people interested in solving optimization problems. Because of the wide (and growing) use of optimization in science, engineering, economics, and industry, it is essential for students and practitioners alike to develop an understanding of optimization algorithms.Knowledgeofthecapabilitiesandlimitationsofthesealgorithmsleadstoabetter understanding of their impact on various applications,and points the way to future research on improving and extending optimization algorithms and software. Our goal in this book is to give a comprehensive description of the most powerful, state-of-the-art, techniques for solving continuous optimization problems. By presenting the motivating ideas for each algorithm, we try to stimulate the reader’s intuition and make the technical details easier to follow. Formal mathematical requirements are kept to a minimum.
Keywords: Optimization